2015
DOI: 10.1109/tip.2015.2487833
|View full text |Cite
|
Sign up to set email alerts
|

Salient Object Detection: A Benchmark

Abstract: We extensively compare, qualitatively and quantitatively, 41 state-of-the-art models (29 salient object detection, 10 fixation prediction, 1 objectness, and 1 baseline) over seven challenging data sets for the purpose of benchmarking salient object detection and segmentation methods. From the results obtained so far, our evaluation shows a consistent rapid progress over the last few years in terms of both accuracy and running time. The top contenders in this benchmark significantly outperform the models identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
312
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,279 publications
(340 citation statements)
references
References 134 publications
2
312
1
Order By: Relevance
“…While supervised approaches, such as those in [45] and [36], have the potential of finding more accurate results, their performance depends on the training process followed and the data that has been exploited for training. Recent works have also indicated that unsupervised saliency detection approaches can compete (or even outperform) supervised methods [43].…”
Section: Probabilistic Saliency Estimationmentioning
confidence: 99%
See 3 more Smart Citations
“…While supervised approaches, such as those in [45] and [36], have the potential of finding more accurate results, their performance depends on the training process followed and the data that has been exploited for training. Recent works have also indicated that unsupervised saliency detection approaches can compete (or even outperform) supervised methods [43].…”
Section: Probabilistic Saliency Estimationmentioning
confidence: 99%
“…For an extensive survey on the recent state-of-the-art salient object detection algorithms, readers are encouraged to see [37].…”
Section: Probabilistic Saliency Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead of surveying the large volume of literature, which is impractical here, we mainly focus on recent bottom-up saliency methods and top-down models, and 1 http://github.com/shenjianbing/saliencytransfer analyze their properties and limitations. We refer the readers to [23] and [24] for more detailed reviews of the saliency models.…”
Section: Related Workmentioning
confidence: 99%